1983
DOI: 10.1073/pnas.80.24.7631
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypolipidemic therapy on cholesterol homeostasis in freshly isolated mononuclear cells from patients with heterozygous familial hypercholesterolemia.

Abstract: Freshly isolated mononuclear leukocytes have been reported to-show changes in cholesterol synthesis and high-affinity degradation of low-density lipoproteins (LDL) that parallel those that occur in the liver. To examine whether hypolipidemic therapy in patients with heterozygous familial hypercholesterolemia influences cholesterol homeostasis in their mononuclear cells we assessed the effects of colestipol and nicotinic acid (alone and in combination) on the rates of high-affinity "SI-labeled LDL degradation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…An increase in LDL degradation in vitro, indicative of increased expression of LDL receptors, has previously been documented in mononuclear leukocytes obtained from FH heterozygotes treated with a BAS. 35 The apparent lack of response of mononuclear leukocyte HMG CoA reductase mRNA to inhibition (statin) and stimulation (BAS) in the present study could be ascribed to various causes. One difference between the present study and that of Powell and Kroon 34 is that we used FH patients, whereas they studied non-FH individuals.…”
Section: Discussionmentioning
confidence: 83%
“…An increase in LDL degradation in vitro, indicative of increased expression of LDL receptors, has previously been documented in mononuclear leukocytes obtained from FH heterozygotes treated with a BAS. 35 The apparent lack of response of mononuclear leukocyte HMG CoA reductase mRNA to inhibition (statin) and stimulation (BAS) in the present study could be ascribed to various causes. One difference between the present study and that of Powell and Kroon 34 is that we used FH patients, whereas they studied non-FH individuals.…”
Section: Discussionmentioning
confidence: 83%
“…Foam cells in atherosclerotic lesions contain large amounts of cholesterol esters and there is considerable evidence that a substantial number of these foam cells originate from monocyte-derived macrophages [8]. Previous studies have indicated that human monocyte derived macrophages (HMDM) demonstrate a pattern of cholesterol homeostasis similar to cholesterol metabolism in the liver [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…16 - 18 For example, the rates of cholesterol synthesis and high affinity receptor-mediated degradation of I 12S -LDL in freshly isolated mononuctear leukocytes from patients with heterozygous familial hypercholesterolemia (FH) were both increased during therapy with the bile acid sequestrant colestipol. 15 Similarty, dietary cholesterol has been shown to depress cholesterol synthesis or HMG CoA reductase activity in freshly isolated mononuclear leukocytes. 1718 Both of these effects parallel those that are known to occur in the liver.…”
mentioning
confidence: 99%